2013
DOI: 10.1371/journal.pmed.1001558
|View full text |Cite
|
Sign up to set email alerts
|

Global Mortality Estimates for the 2009 Influenza Pandemic from the GLaMOR Project: A Modeling Study

Abstract: Lone Simonsen and colleagues use a two-stage statistical modeling approach to estimate the global mortality burden of the 2009 influenza pandemic from mortality data obtained from multiple countries. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
372
4
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(428 citation statements)
references
References 43 publications
17
372
4
16
Order By: Relevance
“…While we were aware that Poisson family models are conventionally used for statistical modeling of count data and incidence rates,21 we considered the mechanism by which influenza incidence leads to deaths and hypothesized that there should be a linear correlation between incidence and mortality 3. We therefore used an identity link rather than a logarithmic link to relate incidence to mortality in our model, as many others have done 3, 4, 6, 10, 11, 12, 13. We used a normal error distribution, but results would have been similar with a Poisson family error distribution as the numbers of deaths each week were not small.…”
Section: Discussionmentioning
confidence: 99%
“…While we were aware that Poisson family models are conventionally used for statistical modeling of count data and incidence rates,21 we considered the mechanism by which influenza incidence leads to deaths and hypothesized that there should be a linear correlation between incidence and mortality 3. We therefore used an identity link rather than a logarithmic link to relate incidence to mortality in our model, as many others have done 3, 4, 6, 10, 11, 12, 13. We used a normal error distribution, but results would have been similar with a Poisson family error distribution as the numbers of deaths each week were not small.…”
Section: Discussionmentioning
confidence: 99%
“…The weekly number of hospitalizations (by date of admission) for each subgroup was modeled as a function of viral activity, seasonality, and trend using a quasi‐Poisson regression model similar to previously published estimates of the influenza burden in Canada (see Appendix S2 for details)6, 7 and internationally 3. The number of hospitalizations attributed to each virus was calculated for each week by subtracting the estimated baseline from the model‐predicted number of hospitalizations.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2003, a regression approach has been widely used in many countries,3, 5 including Canada to estimate the excess burden associated with influenza and other respiratory viruses 6, 7, 8, 9. Because regression estimates are not available in real time, researchers have proposed other methods10, 11 to use surveillance data to predict the full burden in near real time, only some of which have been evaluated at year‐end against a regression approach 6, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…However, global mortality studies have shown that the 2009 influenza A(H1N1) pandemic virus did in fact affect mortality in tropical climate countries 19, 20. Both Dawood and Simonsen estimated high rates of influenza‐associated respiratory death related to the emergence of influenza A(H1N1)pdm09 in some tropical climate countries compared to other parts of the world 19, 20. Specifically, the influenza mortality estimated among <65 years old was higher in South‐East Asia during the pandemic year (2009) when compared with seasonal influenza epidemics 20.…”
mentioning
confidence: 99%
“…Both Dawood and Simonsen estimated high rates of influenza‐associated respiratory death related to the emergence of influenza A(H1N1)pdm09 in some tropical climate countries compared to other parts of the world 19, 20. Specifically, the influenza mortality estimated among <65 years old was higher in South‐East Asia during the pandemic year (2009) when compared with seasonal influenza epidemics 20. In addition, Alonso et al indicated that influenza A(H1N1)pdm09 did not affect mortality rates in Madagascar.…”
mentioning
confidence: 99%